2015
DOI: 10.1007/s11745-015-4098-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Maternal Erythrocyte Long Chain Polyunsaturated Fatty Acids Exist in Early Pregnancy in Preeclampsia

Abstract: The present prospective study examines proportions of maternal erythrocyte fatty acids across gestation and their association with cord erythrocyte fatty acids in normotensive control (NC) and preeclamptic pregnancies. We hypothesize that maternal fatty acid status in early pregnancy influences fetal fatty acid stores in preeclampsia. 137 NC women and 58 women with preeclampsia were included in this study. Maternal blood was collected at 3 time points during pregnancy (16-20th weeks, 26-30th weeks and at deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…To the best of our knowledge, there are no published follow-up data from children born to mothers with preeclampsia in LMICs. Previous studies carried out in our department have demonstrated higher maternal homocysteine, oxidative stress, altered placental angiogenesis and disturbed fatty acid metabolism in women with preeclampsia [27,28,29]. We have also reported altered placental global and gene specific methylation patterns in angiogenic factors in preeclampsia [30].…”
Section: Introductionsupporting
confidence: 69%
“…To the best of our knowledge, there are no published follow-up data from children born to mothers with preeclampsia in LMICs. Previous studies carried out in our department have demonstrated higher maternal homocysteine, oxidative stress, altered placental angiogenesis and disturbed fatty acid metabolism in women with preeclampsia [27,28,29]. We have also reported altered placental global and gene specific methylation patterns in angiogenic factors in preeclampsia [30].…”
Section: Introductionsupporting
confidence: 69%
“…Several maternal characteristics, including gestational age, socioeconomic status, education, smoking and supplement use, have already been shown to affect fatty acid levels [ 63 , 77 ]. In our study, nationality, smoking status, physical activity and DHA supplement intake were found to affect several erythrocyte fatty acid species.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier preliminary study on erythrocyte fatty acid levels in women with preeclampsia ( n = 58) and normotensive controls ( n = 137) at 16–18 weeks of gestation showed a mean difference of 0.3 and standard deviation of 0.8 [49]. We aim to study 100 women with preeclampsia and 200 normotensive women, which will give 87% power to detect a difference of the same magnitude when alpha is kept at 0.05.…”
Section: Methodsmentioning
confidence: 99%